Studying the reality of the general budget for public administrative units in the Kurdistan Region - Iraq and ways to develop it - غازي عثمان محمود; جبار احمد عبد الله (Iraqi Journal for Administrative Sciences, 2025)
This paper aims in general to study and improve the system of public budgeting in Kurdistan region in order to response for international developments in of modern financial system. In achieving this goal the paper review the approaches and methods of property the public budget of the nation, and explain the required components of improving the governmental accounting system in conformity to the implantation, of (program and performance budget) for the nation for both Expenders and Revenues (income). The researches consulted to important result that the trabetional budget has many defects and short coming practically in the level of spending (Expenditures for the previous years in the lack of subjective and scientific standards to link between inputs and outputs. Therefore the researchers lave recommended improvement to take direct action for Applying the recommendation of international monetary funds for improving the government financial system and implantation the program and performance budget for averment units, this methods assists the decision makes to laxer reliable information in order to achieve the optimal utilization for public funds.